Discursivity, difference, and disruption: Genealogical reflections on the consumer culture theory heteroglossia. (June 2013) - Thompson, Craig J; Arnould, Eric; Giesler, Markus
We offer a genealogical perspective on the reflexive critique that consumer culture theory (CCT) has institutionalized a hyperindividualizing, overly agentic, and sociologically impoverished mode of analysis that impedes systematic investigations into the historical, ideological, and sociological shaping of marketing, markets, and consumption systems. Our analysis shows that the CCT pioneers embraced the humanistic/experientialist discourse to carve out a disciplinary niche in a largely antagonistic marketing field. However, this original epistemological orientation has long given way to a multilayered CCT heteroglossia that features a broad range of theorizations integrating structural and agentic levels of analysis. We close with a discussion of how reflexive debates over CCT's supposed biases toward the agentic reproduce symbolic distinctions between North American and European scholarship styles and thus primarily reflect the institutional interests of those positioned in the Northern hemisphere. By destabilizing the north–south and center–periphery relations of power that have long-framed metropole social science constructions of the marginalized cultural "other" as an object of study—rather than as a producer of legitimate knowledge and theory—the CCT heteroglossia can be further diversified and enriched through a blending of historical, material, critical, and experiential perspectives.